STRATEGI PENANAMAN NILAI KEJUJURAN PADA ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA PONTIANAK BARAT - Friska Vinallia Adriani; Marwawi R; Annisa Amalia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to describe the strategy of cultivating the value of honesty in children aged 5-6 years at TK Negeri Pembina West Pontianak. The research method used is a descriptive method of qualitative research form. The subjects in the study were 2 class B teachers at the TK Negeri Pembina West Pontianak. The research location is in the TK Negeri Pembina West Pontianak. The data collection techniques used in this study are observation, interview and recording. The results showed that the strategy of cultivating the value of honesty in children at TK Negeri Pembina West Pontianak, namely: 1.Inquiry Elerning Strategy (increasing the potential for children's thinking), the teacher uses storytelling to instill the value of honesty in children after telling the story the teacher asks questions and answers with children to explore knowledge child. 2. Exemplary strategy, the teacher provides exemplary through habituation to children by teaching children to behave and say good and to accustom children to admit when they are guilty. 3. Strategies to meet the needs of play, the games used by the teacher to instill the value of honesty in children, namely games of hide and seek and snakes and ladders.Keywords: Strategy Inculcating The Value of Honesty